A Woman, a Snake, and a Bear-Woman: An Intertextual Reading of the Garden of Eden Story (gen 2:4b–3:24) In Relation to a Korean Origin Myth - Park, Caroline Choi (Biblical interpretation, 2025)
This article seeks an alternative interpretation of the Garden of Eden story by reading it intertextually with a Korean origin myth, Dangun Shinhwa. Reflecting the animistic Korean indigenous culture, the myth portrays fluid boundaries between humans, animals, and gods, serving to undermine commonly anthropocentric and androcentric interpretations of the biblical story. Cued by animistic aspects of Dangun Shinhwa, the first part of the article rereads Genesis 2 through animism, leading to different interpretations of the characters—human and nonhuman beings and God—and the ontology of their world. Thus informed, the second part reads Gen 3 alongside Dangun Shinhwa, which features a bear who becomes a woman and later the mother of Korean people. The reading yields an alternative meaning to the familiar story about the human loss of connections and soul unawareness, foretelling the tragedy of today’s carno-phallogocentric world.